STUDI ISU AKTUAL PENDIDIKAN ISLAM : PEREMPUAN DALAM LINGKARAN HIDUP MASOKISME - Wafa, Abdul (TARBAWI:Journal on Islamic Education, 2023)
As a result of the modernization of social life in the vortex of human life, the term masochism emerged in women's lives. The term gives the impression that women are identical to objects and targets of violence by men. However, masochism does not encourage women to fight against men as the perpetrators. Masochism itself arises because of internal causes of women themselves and is not purely caused by men. Such as feelings of guilt and defeat, rejecting good behavior, feeling insulted, happy to suffer as long as the person they love is happy, not wanting to appear in public, depending on men, and so on. Islam with its perfect teachings provides an intelligent and educational solution for women to get out of the circle of masochism, namely by emphasizing education that teaches them an egalitarian and ideal life in accordance with human dignity.